The influence of the ethno-territorial factor on the state of physical abilities development of students of Ukrainian educational institutions - Igor Vypasniak; Iryna Ivanyshyn; Vasyl Lutskii; Oleksandra Huzak; Vira Yukhymuk; Ivan Salatenko; Andrii Svatiev (IP Iermakov S.S., 2022)
Background and Study Aim. The development of motor skills depends on the process of physical development, as well as the ethno-territorial and cultural context. The study of inter-ethnic differences can provide information about how different lifestyles and contexts of physical activity can influence the process of motor competence development. This can be a real strategy for developing students' lagging basic motor skills. The purpose of the work is to investigate the ethno-territorial variability of the level of development of physical abilities of students studying at Ukrainian universities. Material and Methods. Data were obtained from cross-sectional surveys from 2014 to 2019. Students of Ivano-Frankivsk National Medical University (Ukraine) (young men, n = 488, age 18-25) from different countries were recruited. Pedagogical testing was carried out using a battery of tests that were recommended by the State Tests of Physical Fitness of the Population of Ukraine and the European Sports Council (Evrofit Test Battery). Assessment of physical fitness of students was carried out on the basis of a combined percentage scale of multi-level gradation with a step of 1%. Experimental data were processed using the SPSS Statistics 17.0 program. Results. In almost all countries (with the exception of India and Tunisia), from 41.2% to 70.0% of students are characterized by a low level of development of cardiorespiratory endurance and speed-power fitness (from 54.4% to 58.3%). More than 50.0% of students from Jordan and Egypt have a low level of speed and strength abilities and flexibility. It was found that students from India and Tunisia have the highest rates (endurance - 75.5-80.8%); from China and Tunisia (speed-power abilities - from 69.1% to 78.8%); from Tunisia (speed -79.8%); from China and Tunisia (flexibility -70%); test participants completed the test; from China (power capacity - 76.7%). Students from European countries showed mostly average and above average level of development of physical abilities. Conclusions. The results of the study indicate the specificity of the development of motor skills of students from different countries, which is manifested in statistically significant differences in the results of test tasks. Students from different countries perform better on those tests that are closer to their known motor experience. This is due to the cultural environment, geographical factor, socio-economic status, as well as the content and goals of the physical education program.